Pedagogical Historiography - Modern State of Directions of Historicf-Pedagogical Researches - Kateryna Binytska (Pedagogical Discourse, 2013)
The article deals with the problems of theory of pedagogical historiography, as one of directions of historic-pedagogical researches. The author reveales theoretical approaches to this problem, interprets the views of other researchers. Considerable attention is payed to illumination of  the views of the modern researchers to the determination of the term «historiography». The functions and methods of pedagogical historiography are determined. In particular, the functions of historiography include: cognitive, methodological, structural and critical, predictive, worldview, paradigm, integration and didactic. Methods of teaching historiography are: study of information sources, historic-structural, historic-genetic, paradigm, personalistic-biographical, terminological analysis.